KETAHANAN PANGAN RUMAH TANGGA BERDASARKAN PENDAPATAN PETANI JAGUNG MANIS DI DESA BULUPOUNTU JAYA KECAMATAN SIGI BIROMARU - Veki Vernando; Sri . Jumiyati; Syaiful Bachri (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2022)
Food is a basic need for humans to survive, and therefore adequate food for everyone is a basic right that deserves to be fulfilled. One of the important indicators affecting the food security status of farmer households is income. This study aims to determine the amount of income obtained from maize farming and the value of household food security of maize farmers in the Bulupountu Jaya Village, Sigi Biromaru District, Sigi Regency. The research was conducted from July to September 2020. The analytical method used is a descriptive based on the farm household income, staple food needs, and local staple food prices. The results showed that the income received by maize farmers for one planting season was IDR 6,384,691.85/farmer or IDR 5,010,159.76/ha with revenue of IDR 10,182,692.31/ farmer or IDR 13,441,153.85/ha. Meanwhile, the total production cost incurred is IDR 3,798,000.46/farmer or IDR 5,010,159.76/ha. The farm household income from outside maize farming comes from livestock businesses amounting to IDR 5,007,692.31 and as a laborer an amount of IDR 5,215,384.61, with a total side income of IDR 10,223,076.92. Farm household food security shows a value greater than 1 (Z>1), amounting to IDR 9,250,776.92, which means that maize farmer households with a side business will have a food security condition in a year and have an excess of IDR.9,250,776.92, to buy necessities other than staple food (rice).